Collective canard explosions of globally-coupled rotators with adaptive coupling. (December 2021) - Ciszak, Marzena; Olmi, Simona; Innocenti, Giacomo; Torcini, Alessandro; Marino, Francesco
Highlights: The paper reports the first evidence of collective canard cycles in a network of phase-oscillators. Canards are explained in terms of geometric singular perturbation analysis of an exact mean-field model. We study the emergence of an effective slow manifold as the size of the network increases. Abstract: Canards, special trajectories that follow invariant repelling slow manifolds for long time intervals, have been frequently observed in slow-fast systems of either biological, chemical and physical nature. Here, collective canard explosions are demonstrated in a population of globally-coupled phase-rotators subject to adaptive coupling. In particular, we consider a bimodal Kuramoto model displaying coexistence of asynchronous and partially synchronized dynamics subject to a linear global feedback. A detailed geometric singular perturbation analysis of the associated mean-field model allows us to explain the emergence of collective canards in terms of the stability properties of the one-dimensional critical manifold, near which the slow macroscopic dynamics takes place. We finally show how collective canards and related manifolds gradually emerge in the globally-coupled system for increasing system sizes, in spite of the trivial dynamics of the uncoupled rotators.